Fibromatosis of the facial skin – case report and review of the literature - Kuśnierz, Piotr; Zapała-Pośpiech, Agnieszka; Wyszyńska-Pawelec, Grażyna; Kosowski, Bogdan (Dermatology Review/Przegląd Dermatologiczny, 2013)
Introduction. Fibromatosis is included in the group of desmoid tumours arising from the musculoaponeurotic structures. These benign fibrous tumours can occur in any part of the body. Although fibromatosis does not metastasize and has no malignant potential, it is known as a locally aggressive neoplasm with a high incidence of local recurrence. Biological behaviour classifies the disease between fibromas and fibrosarcomas. Physical examination reveals a firm, fixed and non tender mass with an ability to spread through fascial planes and to invade the surrounding structures. Objective . Presentation of fibromatosis of the face and literature review. Case report. We present a rare case of fibromatosis of the paranasal, infraorbital and buccal regions in a 24-year-old male patient, who underwent three complete excisions of the lesions. Despite negative margins, recurrence of the tumour was observed in the next few months. For this reason, the last surgical treatment was combined with radiation as an adjuvant therapy. A two-year follow-up confirmed efficiency of this therapeutic method. Conclusions . Surgical treatment combined with radiation is effective in recurrence prevention in patients with fibromatosis of the head and neck. Late, final reconstructions should be conducted after at least 3 years of follow-up without recurrence.